Enhanced field-emission behavior of layered MoS2 sheets - Kashid, Ranjit V.; Late, Dattatray J.; Chou, Stanley S.; Huang, Yi-Kai; De, Mrinmoy; Joag, Dilip S.; More, Mahendra A.; Dravid, Vinayak P. (Small, 2013)
Field emission studies are reported for the first time on layered MoS2 sheets at the base pressure of approximate to 1 x 10(-8) mbar. The turn-on field required to draw a field emission current density of 10 A/cm(2) is found to be 3.5 V/m for MoS2 sheets. The turn-on values are found to be significantly lower than the reported MoS2 nanoflowers, graphene, and carbon nanotube-based field emitters due to the high field enhancement factor (approximate to 1138) associated with nanometric sharp edges of MoS2 sheet emitter surface. The emission current-time plots show good stability over a period of 3 h. Owing to the low turn-on field and planar (sheetlike) structure, the MoS2 could be utilized for future vacuum microelectronics/nanoelectronic and flat panel display applications.